Improvement of key processes through the analysis of value added in technology- based companies a single project productions of the wáter sector in Cuba - Hernández Oro, Reina Maylín (2011)
Fil: Hernández Oro, Reina Maylín. Universidad Central Marta Abreu de Las Villas; Cuba.